The Ethics of Anthropology and Amerindian Research
XVI, 524 p.
Keywords: The decision to publish scholarly findings bearing on the question of Amerindian environmental degradation, warfare, and/or violence is one that weighs heavily on anthropologists. This burden stems from the fact that documentation of this may render indigenous communities vulnerable to a host of predatory agendas and hostile modern forces. Consequently, some anthropologists and community advocates alike argue that such culturally and socially sensitive, and thereby, politically volatile information regarding Amerindian-induced environmental degradation and warfare should not be reported. This admonition presents a conundrum for anthropologists and other social scientists employed in the academy or who work at the behest of tribal entities. This work documents the various ethical dilemmas that confront anthropologists, and researchers in general, when investigating Amerindian communities. The contributions to this volume explore the ramifications of reporting--and, specfically,--of non-reporting instances of environmental degradation and warfare among Amerindians. Collectively, the contributions in this volume, which extend across the disciplines of archaeology, anthropology, ethnohistory, ethnic studies, philosophy, and medicine, argue that the non-reporting of environmental mismanagement and violence in Amerindian communities generally harms not only the field of anthropology but the Amerindian populations themselves.